Financial Fragility with SAM? - GREENWALD, DANIEL L.; LANDVOIGT, TIM; VAN NIEUWERBURGH, STIJN (Journal of Finance, 2021)
ABSTRACT Shared appreciation mortgages (SAMs) feature mortgage payments that adjust with house prices. They are designed to stave off borrower default by providing payment relief when house prices fall. Some argue that SAMs may help prevent the next foreclosure crisis. However, home owners' gains from payment relief are mortgage lenders' losses. A general equilibrium model in which financial intermediaries channel savings from saver to borrower households shows that indexation of mortgage payments to aggregate house prices increases financial fragility, reduces risk‐sharing, and leads to expensive financial sector bailouts. In contrast, indexation to local house prices reduces financial fragility and improves risk‐sharing.